Optimasi Proses Hidrolisis Rumput Laut Ulva Reticulata dengan Pelarut HNO3 untuk Produksi Bioetanol - Sefrinus Maria Dolfi Kolo; Noviana Mery Obenu; Lusitania Kefi; Felicitas F.Fuel (Universitas Andalas, 2023)
One alternative to make biofuels and replace petroleum-based fuels is to convert non-food ingredients from Ulva reticulata seaweed into bioethanol. Seventy percent of the earth's surface is covered by microalgae and seaweeds that can be converted into bioethanol. Ulva seaweed contains 50.3% carbohydrates in the form of heteropolysaccharides such as glucose, arabinose, rhamnose and xylose. Optimization of the seaweed hydrolysis catalyzed by HNO3 using Microwave irradiation was done by varying acid concentration (1, 3, 5, 7%), hydrolysis time (30, 40, 50, and 60 minutes), and hydrolysis temperature (75, 100, 125, 150°C). Fermentation was carried out by varying inoculum concentrations (6, 8, and 10% (v/v)) for 5, 6 and 7 days at a temperature of 30°C and a pH of 4.5. Analysis of the surface texture of the sample was carried out by Scanning Electron Microscopy (SEM). The analysis of reducing sugars concentration was carried out using the dinitrosalicylate (DNS) method. Ethanol analysis was carried out by Gas Chromatography (GC). The results of SEM analysis showed that prior to hydrolysis, the surface morphology of the powder was still compact and intact. Whereas after being hydrolyzed with HNO3 it was seen that the surface texture of the powder suffered significant damage. The hydrolysis results showed that the optimum conditions during the pretreatment of U. reticulata powder was at acid concentration of 7%, reaction time of 50 minutes, reaction temperature of 150°C and 250 watts of power which gave hydrolysate with reducing sugar concentration of 86.5 g/L. Fermentation of the hydrolysate using yeast Saccharomyces cerevisiae produced bioethanol with concentration of 37.2% as analyzed using a gas chromatograph.